(untitled) (Research, Society and Development, 2020)
Objective: To spread knowledge about breast cancer to women in a vulnerable community. Methodology: For the description of this research, we opted for the descriptive and qualitative approach, the type of experience report. The experience took place through the execution of an extension project developed in the city of Coelho Neto, in the state of Maranhão, Brazil, with 40 women and 3 three men. The activities developed were based on Freirian thinking, since it describes that knowledge must be passed on in an integrative and interactive way, making education with the other and not for the other. To support the synthesis of the experience, articles published in the journal Research, Society and Development were selected. Results: When asked about which of the participants had already undergone the mammogram, only two said they had already undergone the exam, the others reported not even knowing where to go to request the referral. There are several factors that lead the individual to develop breast cancer. Invited to describe the AEM, with the support of the material made by them, none of the women (or men) present knew how to perform the technique. Conclusion: The lack of knowledge about breast cancer among women and men participating in the conversation circle showed the fragility of preventing this type of cancer in the municipality where the extension project was developed. There is a need for more spaces that promote health education in order to favor comprehensive community care, as it expands its knowledge.